Improving Activities and Learning Outcomes with The SENANG Model in Primary Students - Fransiska, Nola; Agusta, Akhmad Riandy; Rafianti, Wahdah Refia (Institut Agama ISlam Negeri Palangka Raya, 2024)
This research aims to describe teachers' activities and analyze students' activities and learning outcomes. The type of research used was Classroom Action Research (PTK) which was carried out in 3 meetings. The subjects of this research were class V students at SDN Kuin Cerucuk 5. The type of data used in this research was qualitative and quantitative. The results of the research show that teacher activity received a score of 30 with the criteria